2000
DOI: 10.1111/j.8755-8920.2000.430109.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interferon‐Γ on Secretion of Vascular Endothelial Growth Factor by Endometrial Stromal Cells

Abstract: ES cells produce VEGF, which may contribute to endometrial neovascularization and proliferation. IFN-gamma may play an important role in regulating VEGF production by ES cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
4
22
0
1
Order By: Relevance
“…These cytokines do not increase VEGF expression in stromal cultures (M. L. IruelaArispe, unpublished observations), 17 in fact, one study reported a decrease in VEGF transcripts after 6 hours of stromal cell exposure to IFN-␥. 44 In our endometrial stromal cultures, the positive contributions of estradiol and progesterone to VEGF upregulation were modest, with maximal 1.6-to 1.8-fold increases, as has been reported by others. 13,28,29,45 Although VEGF up-regulation in the secretory phase may be explained by progesterone effects, it is unlikely sex steroids play a direct role on VEGF regulation during postmenstrual repair as circulating estrogen and progesterone levels are physiologically low at this point in the cycle.…”
Section: Discussionsupporting
confidence: 80%
“…These cytokines do not increase VEGF expression in stromal cultures (M. L. IruelaArispe, unpublished observations), 17 in fact, one study reported a decrease in VEGF transcripts after 6 hours of stromal cell exposure to IFN-␥. 44 In our endometrial stromal cultures, the positive contributions of estradiol and progesterone to VEGF upregulation were modest, with maximal 1.6-to 1.8-fold increases, as has been reported by others. 13,28,29,45 Although VEGF up-regulation in the secretory phase may be explained by progesterone effects, it is unlikely sex steroids play a direct role on VEGF regulation during postmenstrual repair as circulating estrogen and progesterone levels are physiologically low at this point in the cycle.…”
Section: Discussionsupporting
confidence: 80%
“…Although it was reported that IFN-g itself could inhibit VEGF expression by endometrial stromal cells 20 and has direct antiproliferative effects on some tumor cell lines, 19 in our animal models, immunization of mice with such dose of DC-IFN-g did not show any significant inhibitory effects on tumor cell-induced angiogenesis and metastasis, suggesting that the enhanced antimetastatic effect of DC-sflk1-IFN-g vaccination was not the direct result of growth inhibition of tumor cells by IFN-g secreted by DC-sflk1-IFN-g. Furthermore, our in vivo T-cell subset depletion experiment showed that the antimetastatic effect induced by DC-sflk1 or DC-sflk1-IFN-g vaccination was CD8…”
Section: Antiangiogenic Cancer Immunotherapy With Gene-modified DC J mentioning
confidence: 97%
“…20 These results make IFN-g an attractive cytokine for DC-based antiangiogenic immunotherapy of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ is classically considered as a pro-inflammatory factor, yet in recent years, multiple studies have found IFN-γ to mediate an immune-modulatory and protective function. For example, in human endothelial cells IFN-γ inhibits the angiogenic activity of VEGF through activation of STAT1 pathway [48], down-regulating VEGF mRNA in a dosage-dependent manner [49]. This may help to inhibit excess angiogenesis process in wet AMD.…”
Section: Is There Any Beneficial Role Of Ifn-γ In Terms Of Protectivementioning
confidence: 99%